2012
DOI: 10.1371/journal.pone.0030954
|View full text |Cite
|
Sign up to set email alerts
|

A T3 and T7 Recombinant Phage Acquires Efficient Adsorption and a Broader Host Range

Abstract: It is usually thought that bacteriophage T7 is female specific, while phage T3 can propagate on male and female Escherichia coli. We found that the growth patterns of phages T7M and T3 do not match the above characteristics, instead showing strain dependent male exclusion. Furthermore, a T3/7 hybrid phage exhibits a broader host range relative to that of T3, T7, as well as T7M, and is able to overcome the male exclusion. The T7M sequence closely resembles that of T3. T3/7 is essentially T3 based, but a DNA fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 48 publications
3
51
0
Order By: Relevance
“…Some of these bottlenecks are already being addressed by the introduction of molecular biology techniques that enable the genetic engineering of phage genomes. For example, phages have been genetically engineered to enhance their performance against biofilms (85), to improve antibiotic activity (86,87), and to expand their host ranges (88)(89)(90)(91). The use of well-defined and purified phage preparations is also crucial for therapeutic applications and for regulatory approval (83,92).…”
Section: Current Challenges Faced By Phage Therapymentioning
confidence: 99%
“…Some of these bottlenecks are already being addressed by the introduction of molecular biology techniques that enable the genetic engineering of phage genomes. For example, phages have been genetically engineered to enhance their performance against biofilms (85), to improve antibiotic activity (86,87), and to expand their host ranges (88)(89)(90)(91). The use of well-defined and purified phage preparations is also crucial for therapeutic applications and for regulatory approval (83,92).…”
Section: Current Challenges Faced By Phage Therapymentioning
confidence: 99%
“…The T3/7 recombinant phage exhibited a broader host range and a better adsorption efficiency than those of either of the wildtype phages, i.e., T3 and T7 (132). Le et al demonstrated that host specificity in P. aeruginosa phages is also tail fiber dependent (60).…”
Section: Engineered Phages With Shifted or Broadened Host Rangesmentioning
confidence: 99%
“…Recent advances in sequencing technologies and genetic engineering have allowed for the design of phages with more predictable and domesticated therapeutic properties. For instance, recombinant phages can be created to have hybrid tail fibers from related phages to broaden bacterial host ranges [26,27]. Moreover, added genes can improve phage diffusion by expressing exopolysaccharide-degrading enzymes specific to target biofilm [26].…”
Section: Synthetic Phage Therapiesmentioning
confidence: 99%